2017
DOI: 10.3892/etm.2017.4754
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine reduces blood-brain barrier permeability associated with enhancement of peripheral cholinergic anti-inflammatory effects for treating traumatic brain injury

Abstract: Abstract. Traumatic brain injury (TBI) is a diverse group of intracranial injuries resulting from external mechanical insults to the brain. While basic and clinical research for TBI has been conducted for decades, it has not identified cost-effective medical interventions for treating TBI. Tetramethylpyrazine (TMP), which is derived from the Chinese herb, Ligusticum chuanxiong Hort (Chuan Xiong), has been clinically used for treating ischemic brain injury for years. However, whether TMP could provide effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Evidence from Shao et al demonstrated that LSZ protected neurons from apoptosis and death induced by oxygen-glucose deprivation [21]. Wang et al uncovered that LSZ played the anti-inflammatory activity in treating traumatic brain injury [22]. In addition, many reports considered that LSZ was an effective cure for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from Shao et al demonstrated that LSZ protected neurons from apoptosis and death induced by oxygen-glucose deprivation [21]. Wang et al uncovered that LSZ played the anti-inflammatory activity in treating traumatic brain injury [22]. In addition, many reports considered that LSZ was an effective cure for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) is an alkaloid found in the roots of Ligusticum chuanxiong Hort (Fig. 1) [18]. It has cardioprotective effects against myocardial IR injury: it limits infarct size and reduces apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the progression of cerebral trauma, the permeability of the blood-brain barrier decreases due to the increase of TNF- α and IL-1 β . Wang et al reported that ligustrazine (20 mg/kg) can decrease the level of TNF- α and IL-1 β in the plasma of a rat model [ 63 ]. Additionally, through the NOS inhibition and the monoamine neurotransmitter modulation, senkyunolide I (16 and 32 mg/kg) showed treatment potential for migraine rats [ 64 ].…”
Section: Protective Effect Of Lcmentioning
confidence: 99%